2014
DOI: 10.5539/jsd.v7n5p128
|View full text |Cite
|
Sign up to set email alerts
|

Development of Common Bean (Phaseolus Vulgaris L.) Production Under Low Soil Phosphorus and Drought in Sub-Saharan Africa: A Review

Abstract: Owing to its nutritional value, especially proteins, carbohydrates, vitamins and micronutrients, common bean (Phaseolus Vulgaris L.) has been recognised as a crop that could ensure food security mostly, in Sub-Saharan Africa, where its productivity is low. Its low productivity is attributed to a milliard of constraints, of which low plant-available phosphorus (P) and limited moisture in soil are among the major limiting factors. Synergistic effects of the two factors are accentuated in Sub-Saharan African regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…The greatest production of pulse crops (70%) is in India, China, and Africa [3,4]. A factor severely limiting the production of pulse crops is water, as pointed out by Peterson et al [5] and Namugwanya et al [6]. A lack of stability of pulse yields is observed not only on dry continents, but in recent years also in the temperate climate conditions characteristic of Europe [7].…”
Section: Introductionmentioning
confidence: 99%
“…The greatest production of pulse crops (70%) is in India, China, and Africa [3,4]. A factor severely limiting the production of pulse crops is water, as pointed out by Peterson et al [5] and Namugwanya et al [6]. A lack of stability of pulse yields is observed not only on dry continents, but in recent years also in the temperate climate conditions characteristic of Europe [7].…”
Section: Introductionmentioning
confidence: 99%
“…The dry seed is an important component of nutrition and food security for millions in the developing world, providing a cheap source of protein (65%), energy (32%), and vital micronutrients (Welch et al, 2000). Common bean is a particularly important crop in Rwanda and western Kenya, where the highest global per capita consumption of 60 kg has been reported (Akibode and Maredia, 2012;Namugwanya et al, 2014). In Uganda, beans provide 21.9% of the protein in the diet, with a per capita consumption of 27 kg (Larochelle et al, 2016).…”
mentioning
confidence: 99%
“…In our study, the response of bean grain yields to fertilizer and the newly introduced conservation farming tillage practices was below the yield potential, notwithstanding the remarkable increase. Other workers [53][54][55][56] have observed that yields from on-farm trials were enhanced by using improved seeds and fertilizers, but yields still remained below the genetic potential. This has been attributed to management factors that contributed to poor early-season vigor, in-season plant loss, and environmental stresses.…”
Section: Potential Versus Actual Bean Grain Yieldmentioning
confidence: 99%